Wanita dalam dunia kewartawanan: profesion, prospek dan masa depan dalam konteks industri persuratkhabaran di Sabah - Lee, Kuok Tiung; Siti Suriani Othman; Liana Mat Nayan; Kalaiarasi Thevakumar (2012)
The emergence of female journalists in Sabah’s local newspapers has broken the hegemony and domination of men in the profession of journalism. However, those female journalists are still facing stereotypical perceptions towards women, particularly on the issue of gender discrimination, exploitation of women and many other feminist issues. This preliminary study was carried out to identify the reasons these women chose to become journalists and to determine the issues and challenges faced by female journalists in the newspaper industry. The findings, gathered through in-depth interviews with 12 female journalists from six newspaper companies, have identified the key factors motivating them to choose journalism to be the flexible working hours; the attractive salaries and bonus payments; and the nature of the role of a journalist, which requires lots of travel, offers good prospects to develop their careers, and also gives them the opportunities to further their studies. In terms of their job responsibilities, the news topics assigned to the female journalists covered various issues, such as society, socio-economic development, and politics affairs. Organization size was found to have an obvious influence on the tasks of female journalists compared to male. Generally, there is not much difference between female journalists and male journalists that can be highlighted as they enjoy equal treatments and benefits. Indeed in certain aspects, female journalists have advantages compare to their male colleagues. This finding also rejects the idea that there is if discrimination against or marginalization of women in journalism.